Application of Quality Matters in Digital Learning in Higher Education (Texas Journal of Multidisciplinary Studies, 2021)
This is the extended research work especially in the COVID: 19 pandemic presenting the application of broad multidimensional reference model of Quality Matters for E-Learning standards for blended courses and full online courses in such a way that learning outcomes of the module could be met. In this research paper the importance and tasks of Quality Matters for the course development and its relationship with E-Learning was defined and analyzed in the learning environment with special reference to Public University (PU) in Gulf for undergraduate students. This study clearly defined that the Reference Model of Quality Matters for E- Learning standards could be applied for all types of Modules such as Supportive, Blended or Full Online in learning paradigm that aid in meeting learning outcomes of the course. Also this study magnified the patterns how QM standards facilitated E-Learning. The reference model of Quality Matters can be applied for all types of modules and program.